PENINGKATAN HASIL BELAJAR SISWA KELAS XII PATISERI MELALUI PENGGUNAAN MEDIA MICROSOFT OFFICE POWER POINT PADA PELAJARAN PKn DI SMK N 6 PADANG - Asnelti, Asnelti (TINGKAP, 2014)
This study aims to improve student learning outcomes at Class XII Patiseri using Microsoft office Power Point media on civics lesson in SMK N 6 Padang. Teachers and as many as 28 students of class XII Patiseri included in this study. Data were collected through observation, field notes, and test results. Then, the data have been analyzed descriptively. This study found that the increase of student learning outcomes by using Power Point media in civics learning at class XII Patiseri SMK N 6 Padang is quite significant. In the first cycle, students who completed their learning outcomes were around 16 (57.14%) of the 28 students; while in the second cycle, students who completed their learning outcomes increased to 21 (75%) of 28 students, and the third cycle students who completed the results learning increased further to 28 (100%). Key Words: Learning media, Microsoft Office Power Point, learning outcomes